Occupational Cancer Protection by Most Recommended International Administrative Control - Zaroushani, Vida; Mousavi Jarrahi, Seyedeh Zahra; Rahimi, Sadra (Asian Pacific Journal of Environment and Cancer, 2020)
Background and purpose: Microwave and radio waves are a class of non-ionizing beams that have a variety of applications in different environments, and uncontrolled exposure to these beams can lead to cancer. Implementation of management measures can result in lower exposure and acceptable efficiency in controlling occupational exposure to these beams. Using a descriptive review, this study examines the most managerial measures recommended by international organizations to control occupational exposure to these beams. Analysis method: Initially, the relevant sciences and reference organizations were identified concerning the research topic. Then, keywords were designed based on the PICO principle. Information published by related organizations that were in the form of a Governmental Document, Legal Rule or Regulation, Publication, Report, Guideline, Manual was reviewed without time limitation in English. Besides, searches were made on two external databases (BING and GOOGLE). Then, the process of reviewing, screening and deleting duplicate, unrelated information as well as retrieving resources was performed. After providing the full text of the relevant material, the process of translating and extracting information related to the research subject was carried out, with the focus on organizations and suggested management measures. This study did not include studies such as animal studies, descriptive studies, empirical studies, meta-analysis, and systematic review. Also, documents with incomplete and obscure information were not used.